Về ước lượng Bayes của tham ẩn hỗn hợp trong mô hình hồi quy phi tuyến nhiều chiều - Quang, Ung Ngọc (Journal of Computer Science and Cybernetics, 2016)
The main aim of this note is to investigate Bayesian estimates of the compound parameter in nonlinear regression models by the functional analysis method.